Facile synthesis and phase stability of Cu-based Na2Cu(SO4)2·xH2O (x = 0–2) sulfate minerals as conversion type battery electrodes. Issue 29 (8th July 2022) - Singh, Shashwat; Neveu, Audric; Jayanthi, K.; Das, Tisita; Chakraborty, Sudip; Navrotsky, Alexandra; Pralong, Valérie; Barpanda, Prabeer
Abstract : Mineral exploration forms a key approach for unveiling functional battery electrode materials. Abstract : Mineral exploration forms a key approach for unveiling functional battery electrode materials. The synthetic preparation of naturally found minerals and their derivatives can aid in designing of new electrodes. Herein, saranchinaite Na2 Cu(SO4 )2 and its hydrated derivative kröhnkite Na2 Cu(SO4 )2 ·2H2 O bisulfate minerals have been prepared using a facile spray drying route for the first time. The phase stability relation during the (de)hydration process was examined synergising in situ X-ray diffraction and thermochemical studies. Kröhnkite forms the thermodynamically stable phase as the hydration of saranchinaite to kröhnkite is highly exothermic (−51.51 ± 0.63 kJ mol −1 ). Structurally, kröhnkite offers a facile 2D pathway for Na + ion migration resulting in 20 times higher total conductivity than saranchinaite at 60 °C. Both compounds exhibited a conversion redox mechanism for Li-ion storage with the first discharge capacity exceeding 650 mA h g −1 (at 2 mA g −1 vs. Li + /Li) upon discharge up to 0.05 V. Post-mortem analysis revealed that the presence of metallic Cu in the discharged state is responsible for high irreversibility during galvanostatic cycling. This study reaffirms the exploration of Cu-based polyanionic sulfates, which while having limited (de)insertion properties, can be harnessed for conversion-based electrode materials for batteries.